Pengaruh Social Media Marketing dan Online Customer Review Terhadap Persepsi Nilai Serta Dampaknya Terhadap Minat Beli Pelanggan Shopee di Bekasi - Nelma Sari; Yasmanto Yasmanto; Grand Angelita; Nisa Istikhomah; Achmad Zharkasih (Jurnal Kajian Ilmiah, 2025)
The digital era has brought significant changes to consumer behavior, particularly in the context of e-commerce. Public interest in online buying systems is heavily influenced by social media marketing and online customer reviews. This is evident in the increased usage of online buying and selling applications in society. This research aims to examine the impact of social media marketing and online customer reviews on perceived value and its subsequent effect on the purchasing intention of Shopee customers. The study was conducted among Shopee customers in the Bekasi area. Data collection involved distributing questionnaires in the form of Google Forms through social media platforms such as Instagram, Facebook, and WhatsApp over a two-week period as the target sampling. There were 53 Shopee customers participating in this study, representing various Shopee membership levels, including classic, silver, gold, and platinum. Data analysis utilized the Partial Least Square (PLS) method processed with SmartPLS-3_64bit software. The analysis steps included testing the outer and inner models. The research findings indicate that social media marketing has a direct, positive, and significant influence on perceived value, while online customer reviews also have a direct, positive, and significant impact on perceived value. Perceived value, in turn, has a direct, positive, and significant effect on purchasing intention. Additionally, social media marketing's impact on purchasing intention shows a significant indirect influence mediated by perceived value, as does online customer reviews on purchasing intention.